A cyclic AMP-responsive DNA-binding protein (CREB2) is a cellular transactivator of the bovine leukemia virus long terminal repeat. - Willems, L (1992)
To gain insight into the cellular regulation of bovine leukemia virus (BLV) trans activation, a lambda-gt11 cDNA library was constructed with mRNA isolated from a BLV-induced tumor and the recombinant proteins were screened with an oligonucleotide corresponding to the tax activation-responsive element (TAR). Two clones (called TAR-binding protein) were isolated from 750,000 lambda-gt11 plaques. The binding specificity was confirmed by Southwestern (DNA-protein) and gel retardation assays. Nucleotide sequence analysis revealed that TAR-binding protein is very similar to the CREB2 protein. It contains a leucine zipper structure required for dimerization, a basic amino acid domain, and multiple potential phosphorylation sites. A vector expressing CREB2 was transfected into D17 osteosarcoma cells. In the absence of the tax transactivator, the CREB2 protein and the cyclic AMP-dependent protein kinase A activate the BLV long terminal repeat at a basal expression level: trans activation reached 10% of the values obtained in the presence of tax alone. These data demonstrate that CREB2 is a cellular factor able to induce BLV long terminal repeat expression in the absence of tax protein and could thus be involved in the early stages of viral infection. In addition, we observed that in vitro tax-induced trans activation can be activated or inhibited by CREB2 depending on the presence or absence of protein kinase A. These data suggest that the cyclic AMP pathway plays a role in the regulation of viral expression in BLV-infected animals.